Combined analysis of metagenome and transcriptome revealed the adaptive mechanism of different golden Camellia species in karst regions - Liu, Jianxiu; Jiang, Haidu; Huang, Yang; Zhong, Lisha; Xu, Qin; Yang, Quanguang; Liu, Shengyuan; Wei, Xiao; Liang, Yu; Chai, Shengfeng (Frontiers in Plant Science, 2023)
Camellia sect. Chrysantha is an important rare and protected plant. Some golden Camellia species grow in karst soil while the others grow in acidic soil. In order to study the adaptation mechanism of golden Camellia to the karst environment, four species of golden Camellia growing in the karst soil (Camellia pubipetal, Camellia perpetua, Camellia grandi, Camellia limoni) and four species growing in the acidic soil (Camellia nitidissima, Camellia euphlebi, Camellia tunghinensis and Camellia parvipetal) were selected for this study. Combined the metagenome and transcriptome, the structure and function of the rhizosphere microbial communities and the gene expression in roots of golden Camellia were analyzed. The results showed that the rhizosphere microbial communities in different golden Camellia were significantly different in abundance of Acidobacteria, Actinobacteria, Candidatus_Rokubacteria, Nitrospirae, Planctomycetes, and Candidatus_Tectomicrobia. The proportion of Candidatus_Rokubacteria was significantly higher in the rhizosphere soil of four species of golden Camellia grown in karst areas, compared to Camellia nitidissima, Camellia euphlebia, and Camellia tunghinensis. The linear discriminant analysis Effect Size showed that Camellia parvipetala was similar to karst species in the enrichment of ABC transporters and quorum sensing. During the transcriptome analysis, numerous up-regulated genes in four karst species including CYP81E, CHS, F3H, C12RT1, NAS, and CAD, were found to be enriched in the secondary metabolite synthesis pathway in the KEGG library, when compared to Camellia tunghinensis. This study provides information for plant adaptation mechanisms on the rhizosphere soil microbial composition and gene expression in secondary metabolic pathways to karst habitats and its distribution in karst areas.